Answer:
Step-by-step explanation:
a^2 + b^2 = c^2
where
a and b are the legs
and
c is the hypotenuse
.
the problem gives the "legs" because the LONGEST leg is always the hypotenuse.
a^2 + b^2 = c^2
1071^2 + 1840^2 = c^2
1147041 + 3385600 = c^2
4532641 = c^2
Answer:a
Step-by-step explanation:
Answer:
44x,
Step-by-step explanation:
you can expand the brackets which equals 18x + 24 (or subtract 24 if the expression is 6(3x-4)) at the end of the equation you will add 2 which would give you 44x
Answer:
2 3/8
Step-by-step explanation: